2006
DOI: 10.1038/sj.bjc.6603278
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of childhood tumours of the central nervous system in Denmark, 1980–1996

Abstract: The registered incidence rate of childhood central nervous system (CNS) tumours has increased in several countries. It is uncertain whether these increases are biologically real or owing to improved diagnostic methods. We explored the medical records of 626 CNS tumours diagnosed in Danish children between 1980 and 1996. Population-based registers were used to extract data on mortality and background population. Temporal patterns were analysed by regression techniques. Most tumours were verified by computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
5
15
1
5
Order By: Relevance
“…Regarding social contacts, the above-mentioned diagnostic delay (Raaschou-Nielsen et al , 2006; ng-Tan and Franco, 2007, 2008; Wilne et al , 2007; Raab and Gartner, 2009) suggests confounding by indication as a potential concern as cases may have attended daycare less often compared with controls because of prodromal symptoms or other factors relating to a latent and undiagnosed CABT. This would lead to an underestimation of the association between social contacts and the risk of CABT.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding social contacts, the above-mentioned diagnostic delay (Raaschou-Nielsen et al , 2006; ng-Tan and Franco, 2007, 2008; Wilne et al , 2007; Raab and Gartner, 2009) suggests confounding by indication as a potential concern as cases may have attended daycare less often compared with controls because of prodromal symptoms or other factors relating to a latent and undiagnosed CABT. This would lead to an underestimation of the association between social contacts and the risk of CABT.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a population‐based study from Denmark (24) of children with CNS tumours diagnosed 1980–1996 showed that the incidence had increased with 2.9%, annually. However, there was an obvious increase of incidence after 1988 which continued in a post hoc analysis 1997–2001 with rates exceeding 4.0/100 000 children.…”
Section: Discussionmentioning
confidence: 99%
“…Os dados relativos à incidência de câncer são disponíveis apenas nos locais que contam com Registros de Câncer de Base Populacional (RCBP). Nas últimas décadas, vários estudos vêm relatando um aumento da incidência de tumores do SNC em crianças e adolescentes 2,4,7,[10][11][12][13] . Alguns autores acreditam que possíveis mudanças relacionadas às exposições ambientais estejam associadas ao aumento das taxas de incidência 14,15 .…”
Section: Introductionunclassified
“…Alguns autores acreditam que possíveis mudanças relacionadas às exposições ambientais estejam associadas ao aumento das taxas de incidência 14,15 . Uma explicação alternativa seria a ampliação do acesso a técnicas diagnósticas não invasivas, assim como mudanças nos procedimentos de registro dos casos ou nas práticas de classificação dos tumores 10,11,13 .…”
Section: Introductionunclassified